The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s11469-019-00121-1
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Interaction Between Time Perception and Gaming: A Narrative Review

Abstract: Compromised time control is a variable of interest among disordered gamers because time spent on videogames can directly affect individuals' lives. Although time perception appears to be closely associated with this phenomenon, previous studies have not systematically found a relationship between time perception and gaming. Therefore, the purpose of this narrative review is to explore how gaming disorder may be associated with time perception. It has been found that gamers exhibit a stronger attentional focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 128 publications
0
9
0
Order By: Relevance
“…Palmer Luckey (founder of Oculus) suggested that the effect could be a result of not having access to real-world environmental cues, like the position of the sun. Distorted time perception has been observed as an effect of conventional gaming (Nuyens et al, 2020), but the influence of VR on time perception has been studied relatively less.…”
Section: Introductionmentioning
confidence: 99%
“…Palmer Luckey (founder of Oculus) suggested that the effect could be a result of not having access to real-world environmental cues, like the position of the sun. Distorted time perception has been observed as an effect of conventional gaming (Nuyens et al, 2020), but the influence of VR on time perception has been studied relatively less.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have proposed that the distortion of subjective time perception is an important part of the psychological state of flow [10, 11]. Such an account usually refers to the feeling of an accelerated passing of time during flow state, and has been measured previously in laboratory conditions [22], as well as in previous studies such as in gaming [34] and music performance [8]. To our knowledge, STR has not been a measure of interest in previous studies on flow state of musical improvisation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proposed that the distortion of subjective time perception is an important part of the psychological state of flow (Csikszentmihalyi, 1975(Csikszentmihalyi, , 1990. Such an account usually refers to the feeling of an accelerated passing of time during flow state, and has been measured previously in laboratory conditions (Im and Varma, 2018), as well as in previous studies such as in gaming (Nuyens et al, 2019) and music performance (Chirico et al, 2015). To our knowledge, STR has not been a measure of interest in previous studies on flow state of musical improvisation.…”
Section: Musical Improvisation As a Target Subjective State?mentioning
confidence: 98%